1963
DOI: 10.1002/app.1963.070070219
|View full text |Cite
|
Sign up to set email alerts
|

Peel adhesion. I. Some phenomenological aspects of the test

Abstract: In the peel test the results strongly depend on some variables related to the teat method such as the thickness of the substrate and of the adhesive, rate of testing, geometrical arrangement in the test, testing temperature, composition of the surrounding medium, and method of sample prepam tion. Generally, these variables will change the effective rheological properties of the substrate or the adhesive and may also influence the effective interfacial bond strength. The present study concentrates on the rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
4

Year Published

1969
1969
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 0 publications
1
39
0
4
Order By: Relevance
“…During these oscillations, transitions from quasistatic to dynamic crack propagation regimes may then develop [2], the latter being prone to trigger fracture front instabilities [3]. The stick-slip oscillations of the detachment front during the peeling of adhesive tape is another outstanding example, extensively studied [4][5][6][7][8][9][10][11][12][13][14][15]. However, it remains nowadays an industrial concern, leading to unacceptable noise levels, damage to the adhesive and mechanical problems on assembly lines.…”
mentioning
confidence: 99%
“…During these oscillations, transitions from quasistatic to dynamic crack propagation regimes may then develop [2], the latter being prone to trigger fracture front instabilities [3]. The stick-slip oscillations of the detachment front during the peeling of adhesive tape is another outstanding example, extensively studied [4][5][6][7][8][9][10][11][12][13][14][15]. However, it remains nowadays an industrial concern, leading to unacceptable noise levels, damage to the adhesive and mechanical problems on assembly lines.…”
mentioning
confidence: 99%
“…In this investigation, 8 = 180°, so the work of adhesion or peel strength is given by [5][6][7][8][9] Here F is expressed in newtons and w is in meters. The experimental values are within 5% error.…”
Section: Determinationmentioning
confidence: 99%
“…One of the notable examples is in adhesively bonded structural joints. Gardon [1963] performed an adhesive peeling test and found that the peeling force decreased as the adhesive layer became thinner. Bascom et al [1975] and Bascom and Cottington [1976] discovered from the tapered double cantilever beam test that the strength of rubbermodified epoxy-bonded specimens increased with the decrease of the adhesive thickness.…”
Section: Introductionmentioning
confidence: 99%